Kerja Raya (JKR) Daerah Maran / Muhammad Iskandar Ikhwan Marzuki - Marzuki, Muhammad Iskandar Ikhwan (Faculty of Civil Engineering, 2022)
Students in several programmes at all levels of study at Institusi Pengajian Tinggi are required to do industrial training (IPT). An industrial training programme has been designed to strengthen the necessary skills in order to increase the employability level of graduates. Students have the chance to learn in the workplace through industrial training programmes, gaining practical experience that improves their marketability. The goal of this programme is to finish the required coursework for the diploma and earn a university degree. Finally, the trainees have the chance to learn more about management and to be fully informed of the site's development. In Industrial Training, I apply all semester courses that have been taught in theory or practical to real world situations. Start the semester differently from any other semester at Jabatan Kerja Raya (JKR) Daerah Maran, as well as the sixth semester to be achieved in order to be successful as well as the course results. From 28 March 2021 to 27 Jully 2022, the total Industrial Training period of 17 weeks. Furthermore, every week I will follow assistant engineer in charge of certain area for site visit. Mainly, the purpose of the site visit is to do site investigation, solving a problem at the site and to see the progress of the construction. Inaddition, there was a time I was given a chance to sketch the measurement of the bridge during the site investigation. Hence, the Bills of Quantities of the project also sketched by me by referring the JKH (Jadual Kadar Harga). Most of the time, we will also refer the JKR Specification of Buildings 2021 as a guideline in construction work. Preparing a document of 'sebutharga' for every project also a great opportunity for me as I can related it with project management. Lastly, during this internship, it really helped me in understanding how the JKR scope work and how important it is in Civil Engineering.